2012
DOI: 10.1186/1476-072x-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Permitted water pollution discharges and population cancer and non-cancer mortality: toxicity weights and upstream discharge effects in US rural-urban areas

Abstract: BackgroundThe study conducts statistical and spatial analyses to investigate amounts and types of permitted surface water pollution discharges in relation to population mortality rates for cancer and non-cancer causes nationwide and by urban-rural setting. Data from the Environmental Protection Agency's (EPA) Discharge Monitoring Report (DMR) were used to measure the location, type, and quantity of a selected set of 38 discharge chemicals for 10,395 facilities across the contiguous US. Exposures were refined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…It is reported that digestive cancer mortality has a close relationship with water quality and distance from rivers (Hendryx et al, 2012). Esophageal cancer mortality had a significant positive correlation with widespread water pollution and a negative correlation with buffer distance from polluted rivers and lakes .…”
Section: Figure 5 Distribution Of Cancer Villages and Main Grain Yiementioning
confidence: 97%
See 1 more Smart Citation
“…It is reported that digestive cancer mortality has a close relationship with water quality and distance from rivers (Hendryx et al, 2012). Esophageal cancer mortality had a significant positive correlation with widespread water pollution and a negative correlation with buffer distance from polluted rivers and lakes .…”
Section: Figure 5 Distribution Of Cancer Villages and Main Grain Yiementioning
confidence: 97%
“…Cancer mortality exhibited higher correlations with water quality grades than with distance from rivers and lakes (Ebenstein, 2012;Hendryx et al, 2012;Gao, 2013;He, 2013;Massaquoi et al, 2014;Zhang et al, 2014).…”
Section: Figure 5 Distribution Of Cancer Villages and Main Grain Yiementioning
confidence: 99%
“…Scholars have associated green spaces with decreased risks of cardiovascular and cerebrovascular diseases, missed abortions, low birth weight, cancer, and mental problems (Barton and Pretty, 2010;Dadvand et al, 2012;Richardson and Mitchell, 2010;Gascon et al, 2016;Sugiyama et al, 2016). On the other hand, industrial area has been associated with increased depression, cancer, low birth weight, and excessive mortality (Cambra et al, 2011;Hendryx et al, 2012;Lopez-Cima et al, 2011). In addition, better health outcomes are observed in neighborhood with greater area devoted to health facilities (e.g., clinics and hospitals) and institutional land (e.g., schools, square, and community centers) (Brown et al, 2009;Mobley et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…About 59% of the articles refer only one cancer site, and 38% refer two or more sites. The remain articles do not refer to a particular cancer site, considering cancer as a whole, or they indicate various types of cancer but did not mentioned exactly which (Bhowmick et al, 2008;Hendryx et al, 2012;Ruktanonchai et al, 2014). Table 2 summarises the frequency of all cancers analysed, classified according to the 9 th revision of International Statistical Classification of Diseases and Related Health Problems (ICD).…”
Section: Cancer By Sitementioning
confidence: 99%